Internal Egg Quality of Eggs from Laying Hens Soaked in Jackfruit Leaf Mixture During Storage at Room Temperature - Prayitno, Agus Hadi; Mustafa, Achmad Yusuf (Jurnal Ilmu-Ilmu Peternakan, 2026)
This study aimed to evaluate the effects of different soaking times in jackfruit leaf (Artocarpus heterophyllus) solutions on the internal quality of layer chicken eggs stored at room temperature. The research material consisted of fresh eggs of the layer chicken strain Brown Lohman and a solution of jackfruit leaves. Eggs were soaked for 0 (control), 12, 24, 36, or 48 hours and then stored at room temperature for 0, 7, 14, or 21 days. The parameters tested were egg weight loss, air cell height, yolk color, white index, yolk index, pH value, and Haugh unit. The data were analysed via analysis of variance (ANOVA), and differences among means were tested via Duncan’s new multiple range test when the effects were significant (p < 0.01). The results showed that soaking eggs in jackfruit leaf mixture slowed the rates of decrease in egg weight, albumen index, yolk index, pH value, and Haugh unit. A longer shelf-life of eggs can increase egg weight loss, air sac height, egg color, and pH but can decrease the albumen index, yolk index, and Haugh unit. Egg soaking for 48 hours was the most effective treatment for preserving internal quality over 21 days of storage at room temperature.